Aristotle's Nicomachean ethics : a critical guide - Miller, Jon, 1970- (Cambridge critical guides., 2011)
"Aristotle's Nicomachean Ethics is one of the most important ethical treatises ever written, and has had a profound influence on the subsequent development of ethics and moral psychology. This collection of newly-commissioned essays, written by both senior and younger scholars in the field, presents a thorough and close examination of the work. The essays address a broad range of issues including the compositional integrity of the Ethics, the nature of desire, the value of emotions, happiness, and the virtues. The result is a volume which will challenge and advance the scholarship on the Ethics, establishing new ways of viewing and appreciating the work for all scholars of Aristotle"--